Comparison of purification processes of natural gas obtained from three different regions in the world - Koyun, Tansel; Kunduz, Mehmet; Öztop, Hakan Fehmi; Ucgul, Ibrahim (Elsevier Science Bv, 2012)
Natural gases obtained from different regions in the world as Scholen-Germany, Saudi Arabia and Iran were purified with a package code and the obtained results were compared in this study. For purification process, both natural gases flowing in a vertical pipe and monoethanolamine (MEA) flowing as a film from the internal surface of a pipe were examined together. Both fluids were flown in a vertical and laminar regime. Binary diffusion coefficients, Schmidt numbers (Sc) and dynamical viscosities were calculated individually for three types of natural gases. It is demonstrated that the chemical absorption method by MEA process is the most appropriate method at high Damkohler (Da) numbers particularly for natural gases containing high concentrations of CO2 and H2S.
Keywords: natural gas; purification; monoethanolamine (MEA)